Characterization of Intrinsic and Doped ZnO Thin-Films Deposited by RF Magnetron Sputtering for Chalcogenide Based Solar Cell Applications - Gupta A.K.S.; Ahamed E.M.K.I.; Quamruzzaman M.; Matin M.A.; Rahaman K.S.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Aluminum coatings; Chalcogenides; Copper compounds; II-VI semiconductors; Infrared devices; Lime; Magnetron sputtering; Metallic films; Optical films; Substrates; Sulfur compounds; Thin film solar cells; Tin compounds; Ultraviolet visible spectroscopy; X ray diffraction analysis; Zinc oxide; Zinc sulfide; Characterization techniques; Copper zinc tin sulphides; Intrinsic and doped zno; Optical and electrical properties; Radio frequency magnetron sputtering; rf-Magnetron sputtering; Soda lime glass substrate; Visible and near infrared; Thin films